2015
DOI: 10.1016/j.addbeh.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Economic stressors and alcohol-related outcomes: Exploring age cohort differences

Abstract: Objectives This study examined processes linking age cohort, economic stressors, coping strategies and two drinking-related outcomes (i.e., past-month drinking and problematic drinking). Methods Structural equation models were conducted utilizing data from a national survey. Results Findings revealed the associations between economic stressors and both past-month drinking and problematic drinking were significantly greater for members of the millennial cohort compared to baby boomers. These effects are par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In addition, based on reported age and date of examination, participants were placed into four birth year cohorts, because a cohort effect independent of age has been observed in the literature pertaining to drinking habits (47). Specifically, participants were placed into the following birth cohorts: Silent (born ≤1942), Baby Boomers (born 1943-1960), Generation X (born 1961-1981), and Millennials (born ≥1982) (48,49).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, based on reported age and date of examination, participants were placed into four birth year cohorts, because a cohort effect independent of age has been observed in the literature pertaining to drinking habits (47). Specifically, participants were placed into the following birth cohorts: Silent (born ≤1942), Baby Boomers (born 1943-1960), Generation X (born 1961-1981), and Millennials (born ≥1982) (48,49).…”
Section: Methodsmentioning
confidence: 99%
“…This may increase the perceived precariousness of employment among younger downsizing survivors compared to older downsizing survivors. Second, some evidence exists that organizational downsizing, and economic hardship more generally, are more strongly associated with negative affect and alcohol use among younger individuals than among older individuals (Brown, Richman, & Rospenda, 2015; Lahner et al, 2014; Mirowsky & Ross, 2001). For example, Lahner et al (2014) reported that exposure to organizational downsizing was positively related to psychological distress among younger workers (18–36 years old), but was unrelated to psychological distress among older workers (37–66 years old).…”
Section: Introductionmentioning
confidence: 99%
“…Based on this literature, our general thesis is that politically oriented coping may be particularly relevant to people with physical impairments because it taps into a number of active coping techniques that are sometimes unavailable to them. For example, politically oriented coping is characterized by increased awareness of an issue, support seeking, and problem solving—and all these strategies are found to be protective against problem drinking and other negative health outcomes in general populations (Brown, Richman, & Rospenda, 2015; Richman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, research in the general population demonstrates that baby boomers compared with younger age cohorts are (a) more likely to engage in political activities which challenge the status quo (Caren, Ghoshal, & Ribas, 2011; Jennings, 1987) and (b) less likely to consume alcohol in response stressful circumstances (Aseltine & Gore, 2000; Brown et al, 2015; Ruhm & Black, 2002). First, the baby boomers came of age in the late 1960s and 1970s, within the context of active civil rights, women’s, antiwar, and countercultural social movements.…”
Section: Introductionmentioning
confidence: 99%